Performance of Culture Using a Semi-Automatic Needle as a Novel Tool for Collecting Lymph Node Samples for the Diagnosis of Canine Visceral Leishmaniasis - Artur Augusto Velho Mendes Júnior; Fabiano Borges Figueiredo; Luiz Cláudio Ferreira; Lucas Keidel; Renato Orsini Ornellas; Adilson Benedito Almeida; Fernanda Nunes Santos; Luciana de Freitas Campos Miranda; Andreza Pain Marcelino; Sandro Antonio Pereira; Rodrigo Caldas Menezes (Animals)
Zoonotic visceral leishmaniasis is caused by Leishmania (Leishmania) infantum and dogs are the main domestic reservoir. This study compared the performance of parasitological tests using semi-automatic needle puncture (SANP) for collecting popliteal lymph node samples with samples collected from the same lymph node by fine needle aspiration puncture (FNAP) and by necropsy for the diagnosis of canine visceral leishmaniasis (CVL). Popliteal lymph node samples were collected from 30 CVL-seropositive dogs from an endemic region in Brazil. After clinical examination and euthanasia, samples were collected from the same lymph node by SANP, FNAP, and necropsy. The reference tests were culture, immunohistochemistry, and histopathology. Positivity for Leishmania spp. was 70% for immunohistochemistry and 33.3% for histopathology. Culture positivity using the different sampling techniques was 77% for necropsy (87% in the first week), 73% for FNAP (82% in the first week), and 63% for SANP (95% in the first week). The combination of SANP and culture proved to be an alternative for the diagnosis of Leishmania spp. in the lymph node samples of dogs because of its high positivity rate and because it is more practical and faster and has a shorter time to positivity by culture when compared to FNAP and necropsy sampling.